Gigabit broadband all-optical indoor far-end coverage - Wenfa YAN; Feng CHEN (Dianxin kexue)
The indoor wireless local area network has the problem of uneven signal coverage.Moreover, a mismatch between the wireless bandwidth and the incoming broadband rate exists.The research status of wideband indoor wireless coverage was provided with traditional technologies.A new signal coverage technology combining the optical gateway and remote extension covering equipment, using the optical fiber as the transmission medium, was proposed.Experimental results on two examples show that uniform indoor wireless signal coverage and a gigabit level of the rate can be achieved when using the proposed technology.